Предмет: Алгебра,
автор: sonyamyskova
Решите уравнение ;
(2y-3)(3y+1)+2(y-5)(y+5)=2(1-2y)^2+6y
Ответы
Автор ответа:
0
(2y-3)(3y+1)+2(y-5)(y+5)=2(1-2y)²+6y
8y²-7y-53=2(4y²-y+1) -раскрываешь скобки
-5y - 55=0 приводишь подобные
- 5y = 55
y=-11 получаешь ответ
8y²-7y-53=2(4y²-y+1) -раскрываешь скобки
-5y - 55=0 приводишь подобные
- 5y = 55
y=-11 получаешь ответ
Похожие вопросы
Предмет: География,
автор: Аноним
Предмет: Русский язык,
автор: tmarkha602
Предмет: Алгебра,
автор: Kira2521
Предмет: Математика,
автор: emakhsudova
Предмет: Химия,
автор: смурфетта11